Nepalese Economy: Obsolescence, Underpinnings and Approaches to Sustainable Development - Dahal, Madan Kumar (Economic Journal of Nepal, 2015)
Nepalese economy, largely a subsistence as well as high-cost economy with no direct access to sea for expanding international trade and limited transit facilities, rising interest rate on lending, high tax burden, and costly doing business, is passing through a downswing phase circumscribed by poverty and stagnation. The economy is strangulated by sluggish economic growth rate, poor governance and rampant corruption, where a majority of the people lives in abject poverty struggling for their survival. The international comparison illustrates that Nepal’s economy is conspicuously trailing behind other member countries in the SAARC region. Prolonged transition engulfed by growing risks and uncertainties with increasing inefficiency, corruption and political entrenchment jeopardized the entire prospects for economic development. In addition, the respective governments in the past and to-day are terribly engaged in managing the crisis with little emphasis and priority to resolving crucial economic issues. Investment is not a constraint to growth in Nepal, but lack of visionary and determined leadership with strong political commitment to fulfill aspirations of the common people is detrimental to economic progress and prosperity in Nepal. The vision or mission of Nepalese economy should be to build a strong economic nation-state through active participation of the people ensuring a high quality of life to each individual and household within given timeframe. The primary objectives of Nepalese economy should be to increase the magnitude of GNI from a diminutive US 13 billion (2009) to US 100 billion and transform the economy from extremely low GNI per capita (US 440) to a higher GNI per capita (US 3,000) at par with middle income countries by achieving a high, sustainable, broad-based, and inclusive economic growth and eliminating absolute poverty by 2025 and, ultimately, make Nepal the “Switzerland” of Asia. Despite numerous structural constraints, there are ample opportunities that Nepal could tremendously gear up the economy by stimulating its major foundations comprising hydropower, tourism, biodiversity and remittances through foreign employment in cooperation with the private sector. Economic Journal of Nepal Vol. 34, No. 2, Issue no. 134, 2011